Mahāvīrasvāmīno antima upadeśa "Uttarādhyayanasūtra" no chāyānuvāda - Paṭela, Gopāladāsa Jīvābhāī, 1905- (Śrī Puñjābhāī Jaina granthamāḷā ;, 1937)
On the teachings of Mahāvīra; based on Uttarajjhayaṇa, Jaina canonical work.